2001
DOI: 10.1007/bf02721838
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual development in relation to nutritional status

Abstract: The present study was conducted on 180 children in the age group 5-10 years. These children were divided accordingly their ages into 3 sub-groups i.e. 5-6, 7-8 and 9-10 years respectively. In each group 60 children were studied. For the assessment of perceptual skills each child was tested with the help of Picture Ambiguity Test. Responses to the ambiguous cards were scored with respect to time taken to react in each card and ability of the child to perceive figure and ground relationship i.e. centration and d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Another study conducted in Philippines adolescents showed that mental ability of adolescents with good nutritional status was significantly higher than that of adolescents with poor nutritional status, as a whole, even when family income and mental ability were controlled [11]. Similarly, study conducted on perceptual development of adolescents in relation to nutritional status with the help of picture ambiguity test (PAT) reported that there was a significant difference in the performance of well nourished and undernourished adolescents during this test [44]. Similar study conducted on influence of malnutrition on social maturity, visual motor coordination and memory of rural school children in Varanasi district revealed that verbal performance and mean IQ score decreased with severity of malnutrition [45].…”
Section: Discussionmentioning
confidence: 99%
“…Another study conducted in Philippines adolescents showed that mental ability of adolescents with good nutritional status was significantly higher than that of adolescents with poor nutritional status, as a whole, even when family income and mental ability were controlled [11]. Similarly, study conducted on perceptual development of adolescents in relation to nutritional status with the help of picture ambiguity test (PAT) reported that there was a significant difference in the performance of well nourished and undernourished adolescents during this test [44]. Similar study conducted on influence of malnutrition on social maturity, visual motor coordination and memory of rural school children in Varanasi district revealed that verbal performance and mean IQ score decreased with severity of malnutrition [45].…”
Section: Discussionmentioning
confidence: 99%
“…Solvent-Free Synthesis of New OxoazetidinesSeveral new 4-aryl-3-chloro-1-[(5-nitroindazol-1-yl)acetamido]-2-oxoazetidines have been synthesized by a four-step sequential procedure[179] (Scheme 4.14). All steps involving neutral reactants under solvent-free conditions (consequently via polar TSs) were realized under the action of MW activation with serious improvements in yields and important reductions in reaction times.…”
mentioning
confidence: 99%